The Specter of Oppression and National Identity in Hobomok - Alex McDonnell (European Journal of American Studies)
Lydia Maria Child’s Hobomok (1824) advances a national model predicated on tolerance and inclusivity. The novel suggests that the oppressive strictures of Puritanism derive from the psychical trauma of banishment from England. This compels the protagonist Mary to rebel against Salem’s social codes by marrying Hobomok. Her elopement and later return as an accepted member of the community are implicated in Child’s national vision of tolerance. However, the novel’s resolution is ethno-centric as Hobomok chooses self-imposed exile while his son with Mary loses his racial identity. Exploring Child’s narrative through a postcolonial psychoanalytic lens reveals how her narrative reflects upon American identity formation which draws upon yet disavows the Native figure in nineteenth-century literature. Significantly, Child’s novel anticipates a space for Native American subjectivity, which conflicts with her national vision and casts doubt on the legitimacy of the American State.